Audit of Child and Adolescent Admissions to an Adult Psychiatric Unit: Addressing Service Gaps and Legal Compliance - Praveen Kumar; Kevin Edassery; Parth Dhirawani; Soma Tadi (BJPsych Open)
Aims: Guidance from the Mental Welfare Commission for Scotland (2013) and the Scottish Government’s Best Practice Guideline for Admission to Adult Mental Health Wards for Under 18s (2013) states that young people should be admitted to age-appropriate settings, with admission to adult psychiatric units occurring only in exceptional circumstances. The United Nations Convention on the Rights of the Child (UNCRC) also advocates for age-specific mental health services.